Síndrome opsoclonus-mioclonus-ataxia: relato de caso - Rosiane Souza Rosse; Maíne Vidal Macedo; Tatiana Guimarães de Noronha; Maria Dolores Salgado Quintans; Alexandre Ribeiro Fernandes (Sociedade Brasileira de Pediatria, 2023)
Opsoclonus-myoclonus-ataxia syndrome (AOM), also known as Kinsbourne syndrome, is a rare neurological disease in childhood, clinically characterized by rapid, irregular and multidirectional eye movements, myoclonic movements in the trunk, face and / or extremities and ataxia. Irritability and disturbances in the sleep cycle can be observed. There are idiopathic cases that have been correlated with viral infections or with the presence of neuroblastoma. As the diagnosis is clinical and there is great variability and heterogeneity in the presentation of cases, an individualized therapeutic approach is considered the best option. This article aims to present the case of an infant, diagnosed with AOM syndrome after a prodromal episode of viral infection of the upper airways. To rule out the presence of an associated hidden neuroblastoma, imaging exams, a study of cerebrospinal fluid and measurement of vanillmandelic acid were performed. The immunological treatment has proven to be effective and consisted of the administration of corticosteroids, intravenous immunoglobulin and monoclonal antibody rituximab.